Dihydroquercetin supplement alleviates colonic inflammation potentially through improved gut microbiota community in mice. Issue 22 (21st October 2021) - Wan, Fan; Han, Hui; Zhong, Ruqing; Wang, Mengyu; Tang, Shanlong; Zhang, Shunfen; Hou, Fujiang; Yi, Bao; Zhang, Hongfu
Abstract : This study shows that DHQ supplementation in the diet can increase the anti-inflammatory capacity potentially by modulating the gut microbiota community in DSS-induced colitis mice. Abstract : The purpose of the current study was to investigate the effect of dietary dihydroquercetin (DHQ) supplementation on dextran sodium sulfate (DSS)-induced colitis in mice. Mice were given DHQ supplementation (3 g kg −1 ) throughout the study, starting 14 days prior to DSS treatment for 1 week followed by 2 days without DSS. The results showed that dietary DHQ supplementation restored DSS-induced disease activity index (DAI), colon length and histopathology scores of the colon tissue. Additionally, supplementation with DHQ reduced the pro-inflammatory cytokine levels, and enhanced the level of IL-10 in the serum. qPCR results indicated that DHQ supplementation significantly downregulated IL-1β, IL-6, and TNF-α, and upregulated IL-10 gene mRNA expression. Western blot results proved that DHQ supplementation upregulated ZO-1 and occludin levels. Using amplicon sequencing technology, 16S rRNA sequencing results showed that DHQ supplementation increased the fecal Firmicutes / Bacteroidetes ratio and the relative abundance of Lactobacillus and Dubosiella, and decreased the relative abundance of Bacteroidetes . Additionally, DHQ supplementation restored the decreased fecal acetic acid and butyric acid concentrations in DSS-induced colitis mice. Besides, Spearman's correlation analysis showed that Dubosiella was positively correlated with the butyric acid level and Bacteroidetes was positively correlated with the mRNA expression of IL-1β and IL-6 . Both Lactobacillus and Dubosiella showed a negative correlation with the mRNA expression of IL-1β, IL-6, and TNF-α, and Dubosiella was positively correlated with IL-10 . In summary, it was found that DHQ supplementation alleviated DSS-induced colitis which may be potentially associated with altered fecal microbiota communities in mice.